Optimization Strategy for Restaurant Tax Collection in UPT Region VI Regional Revenue Agency of Medan City - Ginting, Dea Cindi Amelia; Aisyah, Siti (PT Maju Malaqbi Makkarana, 2025)
Revenue Agency. Restaurant tax is one source of regional income that has great potential in increasing regional original income (PAD). However, in its implementation, there are various challenges such as low taxpayer compliance, lack of supervision, and the effectiveness of the collection system that still needs to be improved. The research method used is a quantitative approach with secondary data analysis from restaurant tax revenue reports and interviews with related parties. The results of the study indicate that the implementation of strategies such as digitalization of the tax collection system, increased supervision and sanctions, and education for taxpayers significantly increased restaurant tax revenue. The data shows an increase in the number of registered restaurants and tax revenue from year to year after the optimization strategy was implemented. These findings support the theory that optimizing the tax system through a technological approach and increasing compliance can increase the effectiveness of tax revenue. Therefore, it is recommended that local governments continue to develop more innovative strategies to ensure taxpayer compliance and increase PAD sustainably